Development of Pt/Au‐Co composite electrode as a highly durable and efficient electrocatalyst for methanol electro‐oxidation in alkaline media. (22nd May 2022) - Begum, Humayra; Rahman, Mohammed M.; Hasnat, Mohammad A.
Summary: Pt metal is well known for exhibiting superior catalytic activity towards methanol electro‐oxidation process but, it is highly poisoned by the intermediate carbonaceous species (CO) which degrade the catalytic activity over time. In this regard, a noble trimetallic electrode was prepared by modifying an unsupported polycrystalline Pt electrode with a mixture of Au and Co through a simple, one‐step electrochemical deposition technique for investigating the methanol electro‐oxidation (MEO) process in alkaline media. Cyclic voltammetric experiment has revealed that the as‐prepared electrode exhibited more than 50% greater stability than those of polycrystalline Pt ((poly) Pt) and Pt/Au electrodes. Moreover, the ratio of forward MEO oxidation peak current and corresponding backward peak current (If /Ib ) was found to be greater for Pt/Au‐Co than (poly) Pt electrode suggesting substantial resistance of the catalyst for CO adsorption. The XPS analysis has demonstrated that Co existed on the electrode surface as Co(II) oxide which is assumed to enhance the stability of Pt/Au‐Co by removing CO species. A relatively smaller Tafel slope (130 mV/dec) was also obtained with Pt/Au‐Co than that of commercially available carbon‐supported Pt catalyst and, the oxidation process was observed to follow half order kinetics concerning methanol. Abstract : Methanol electro‐oxidation on Pt/Au and Pt/Au‐Co catalysts.